Poster Abstract: An Iterative Approach for Non-Line-of-Sight Error Mitigation in UWB Localization - Park, Jiwoong; Imran, Sajida; Ko, Young Bae; Lee, Chang Eun; Park, Sang Joon (Proceedings - 17th ACM/IEEE International Conference on Information Processing in Sensor Networks, IPSN 2018, 2018)
Ultrawideband (UWB) based localization has the potential to be used in a variety of applications due to its high accuracy. For robust and high performance in real environment, the most challenging issue is the detection and mitigation of noise from non-line-of-sight (NLOS) signals. Current researches use channel state information, particle or Kalman filter, and statistics based approaches for the NLOS noise detection and mitigation. These solutions show high accuracy in some applications; however, they need additional hardware and work in static environment only. We propose an NLOS mitigation algorithm that does not need any additional hardware andworks in dynamic environment with mobile obstacles. The main idea of the algorithm are to estimate the NLOS bias by repetitively comparing the intersection of the hyperbolas with intersections of circles. The proposed approach is tested for Decawave UWB testbed. Experimental results show that the proposed scheme works well in different dynamic scenarios as compared to the localization scheme without NLOS noise mitigation.
Keywords: Dynamic environments; Iterative approach; localization; Localization schemes; Nlos mitigations; Non-line of sight error mitigation; Real environments; Static environment; localization; NLOS mitigation; UWB